2014
DOI: 10.1051/0004-6361/201423724
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the EUV spectra of optically thick boundary layers of dwarf novae in outburst

Abstract: Context. Disk accretion onto weakly magnetized white dwarfs (WDs) in cataclysmic variables (CVs) leads to the formation of a boundary layer (BL) between the accretion disk and the WD, where the accreted matter loses its excess kinetic energy and angular momentum. It is assumed that angular momentum is effectively transported in the BL, but the transport mechanism is still unknown. Aims. Here we compute detailed model spectra of recently published optically thick one-dimensional radial BL models and qualitative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 98 publications
(171 reference statements)
1
18
0
Order By: Relevance
“…) support this interpretation. Theory predicts that the transition from mostly optically thin to mostly optically thick should occur at accretion rates of about 10 −9 M ⊙ yr −1 for a 1 M ⊙ WD (Popham & Narayan 1995) or even lower values as proposed by Suleimanov et al (2014). The accretion rate before the optical brightening was therefore likely smaller than a few 10 −9 M ⊙ yr −1 .…”
Section: The Boundary Layer and Unstable Diskmentioning
confidence: 85%
See 1 more Smart Citation
“…) support this interpretation. Theory predicts that the transition from mostly optically thin to mostly optically thick should occur at accretion rates of about 10 −9 M ⊙ yr −1 for a 1 M ⊙ WD (Popham & Narayan 1995) or even lower values as proposed by Suleimanov et al (2014). The accretion rate before the optical brightening was therefore likely smaller than a few 10 −9 M ⊙ yr −1 .…”
Section: The Boundary Layer and Unstable Diskmentioning
confidence: 85%
“…A sudden change in the accretion rate can manisfest itself through a brightening in optical/UV and an X-ray fading. Theory predicts a threshold above which the boundary layer will be optical thick to its own radiation and the observed spectrum will be blackbody-like, while below this threshold the spectrum will be that of an optically thin thermal plasma (e.g., Narayan & Popham 1993;Suleimanov et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…estimated the mass of the WD assuming that the boundary layer was optically thin and therefore the plasma maximum temperature was set by the mass of the WD. Recently,Ducci et al (2016), claimed that the value ofṀ found from the modeling of INTEGRAL + Swift/XRT and Suzaku data would require a mostly optically thick boundary layer in the theoretical framework derived byPopham & Narayan (1995),and Suleimanov et al (2014),; they therefore proposed an alternative scenario in which the X-ray emission is produced in a magnetically channeled flow, analogous to cataclysmic variables of the intermediate polar type and constrained the WD mass to M WD = 0.9-1.1 M ⊙ .…”
mentioning
confidence: 99%
“…The material in the inner disk of nonmagnetic Cataclysmic Variables (CVs) initially moving with Keplerian velocity dissipates its kinetic energy in order to accrete onto the slowly rotating WD creating a boundary layer (BL) (see Warner 1995, Kuulkers et al 2006. Standard accretion disk theory predicts half of the accretion luminosity to originate from the disk in the optical and ultraviolet (UV) wavelengths and the other half to emerge from the boundary layer as X-ray and/or extreme UV (EUV)/soft X-ray emission which may be summarized as L BL ∼L disk =GM W DṀacc /2R W D =L acc /2 (Lynden-Bell & Pringle 1974, Godon et al 1995, Suleimanov et al 2014. During low-mass accretion rates it is expected that,Ṁ acc <10 −(9−9.5) M ⊙ , the boundary layer is optically thin (Narayan & Popham 1993, Popham 1999 emitting mostly in the hard X-rays (kT∼10 (7.5−8.5) K).…”
Section: For a Review On Mcvs)mentioning
confidence: 99%